The equation is: s=se+sp+c

I need to solve for s

I have been out of school for a while and I am embarrassed to admit I forget how to do this...

I know the solution is: s= -c/(p+e+1)

I just forget how to get there.

Please help, thanks

The equation is: s=se+sp+c

I need to solve for s

I have been out of school for a while and I am embarrassed to admit I forget how to do this...

I know the solution is: s= -c/(p+e+1)

I just forget how to get there.

Please help, thanks

I need to solve for s

I have been out of school for a while and I am embarrassed to admit I forget how to do this...

I know the solution is: s= -c/(p+e+1)

I just forget how to get there.

Please help, thanks

go down about 2/3 on this page and use the "trick" they talk about like t his:

s=se+sp+c

s-se-sp=c

s(1-e-p)=c

then divide

s=se+sp+c

s-se-sp=c

s(1-e-p)=c

then divide

Thank you, I feel pretty stupid for having missed that.

I actually had the equation down to s-se-sp=c but had a brain block that wouldnt allow me to go further.

I actually had the equation down to s-se-sp=c but had a brain block that wouldnt allow me to go further.